2023
DOI: 10.3390/ani13111790
|View full text |Cite
|
Sign up to set email alerts
|

One Health Approach: Invasive California Kingsnake (Lampropeltis californiae) as an Important Source of Antimicrobial Drug-Resistant Salmonella Clones on Gran Canaria Island

Abstract: The increase in the reptile population has led to a rise in the number of zoonotic infections due to close contact with reptiles, with reptile-associated salmonellosis being particularly relevant. California kingsnake invasion not only threatens the endemic reptile population of the island of Gran Canaria (Spain) but also poses serious public health problems by spreading zoonotic pathogens and their antimicrobial resistance (AMR) to the environment. Thus, the aim of this study was to assess the occurrence, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In Gran Canaria, Monzón Moreno et al reported a 100% (17/17) Salmonella spp. infection in the endemic lizard Gallotia stehlini [81], and Santana-Hernández et al reported a prevalence of 20.5% in California Kingsnake (L. californiae) on the same island [82].…”
Section: Salmonella Sppmentioning
confidence: 99%
“…In Gran Canaria, Monzón Moreno et al reported a 100% (17/17) Salmonella spp. infection in the endemic lizard Gallotia stehlini [81], and Santana-Hernández et al reported a prevalence of 20.5% in California Kingsnake (L. californiae) on the same island [82].…”
Section: Salmonella Sppmentioning
confidence: 99%
“…Several research studies highlight the importance of NTCAs, such as reptiles, as they can act as reservoirs and sources of Salmonella infection [5,6], a bacterium that is recognised by the World Health Organisation (WHO) as one of the priority pathogens with higher antimicrobial resistance (AMR) worldwide, which needs to be studied and monitored [7]. In fact, numerous outbreaks have occurred in recent years due to the close contact between these animals and their owners, causing serious disease or even death in at-risk populations such as immunocompromised patients, children or the elderly [5,8]. However, little is known about the importance of this pathogen in NTCA small mammals, even though the population of these animals, such as rabbits, guinea pigs, ferrets or mice, among others, is estimated at 29 million of the 340 million companion animals in European households [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the increase in the private ownership of reptiles has led to a rise in the number of zoonotic infections [10][11][12]. Additionally, rodents and birds act as Salmonella amplifiers, playing an essential part in the dissemination of bacteria on farms [13].…”
Section: Introductionmentioning
confidence: 99%